VALIDITY OF ANDROID-BASED DIGITAL COMIC MEDIA IN LEARNING PRINTING GRAPHIC DESIGN FOR VOCATIONAL STUDENTS - Rahmadani, Ade Fitri; -, Ambiyar; Syah, Nurhasan; Suryani, Karmila; Lubis, Vifra Marita (Jurnal Ipteks Terapan, 2024)
The learning process is an effort made by a teacher to teach students to achieve learning goals. The attractiveness of the learning media used by teachers is one of the things that can increase students’ interest in learning. This research aims to determine the validity of the development of Android-based digital comics in the Print Graphic Design subject at SMKN 1 Gunung Talang. The research method used is quantitative descriptive. The research instrument includes validator sheets from media experts and material experts. The validity analysis of digital comics was validated by 1 media expert and 1 material expert. The results of media validation from the media expert aspect obtained a value of 91% and the results of data analysis from instruments that had been filled in by material experts obtained a value of 87%. From these two results, the media developed is declared valid. So it can be concluded that digital comics in the Print Graphic Design subject are valid as learning media. However, further research stages must still be carried out so that this learning media can be used in the teaching and learning process by looking at the user aspect